2017
DOI: 10.1007/s11356-017-9312-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity in adult residents in mineral coal region—a cross-sectional study

Abstract: The present study assessed the DNA damage in environmentally exposed volunteers living in seven municipalities in an industrial coal region, through the use of the comet assay with blood cells and the micronucleus test with buccal cells. Blood and buccal smears were collected from 320 male volunteers living in seven cities inserted in a coal region. They were ages of 18 and 50 years and also completed a questionnaire intended to identify factors associated with DNA damage through a Poisson regression analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…After informed consent was obtained from each individual, an established questionnaire (Da Silva Pinto et al, 2017) was applied to obtain information regarding socioeconomic and life habits of all participants working in the hospital department. Socioeconomic information and life habits included sex, age, annual income, smoking, alcohol consumption, drug use (for both medical and recreational purposes), chimarrão consumption (typical local drink based on yerba mate) medical history, family cancer incidence or genetic predisposition, number of X-rays exposure throughout life (how many times the participant had X-ray used for a diagnostic purpose), and X-ray exposure in the past 12 months, for own medical purpose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After informed consent was obtained from each individual, an established questionnaire (Da Silva Pinto et al, 2017) was applied to obtain information regarding socioeconomic and life habits of all participants working in the hospital department. Socioeconomic information and life habits included sex, age, annual income, smoking, alcohol consumption, drug use (for both medical and recreational purposes), chimarrão consumption (typical local drink based on yerba mate) medical history, family cancer incidence or genetic predisposition, number of X-rays exposure throughout life (how many times the participant had X-ray used for a diagnostic purpose), and X-ray exposure in the past 12 months, for own medical purpose.…”
Section: Methodsmentioning
confidence: 99%
“…DNA damage was detected by the comet assay according to the basic alkaline technique of Singh et al (1988) with modifications by Pinto et al (2017). First, blood samples (15 µL) were mixed with low-melting point agarose at 37°C and embedded on two microscopes slides previously coated with normal melting-point agarose processed at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…To identify micronuclei the criteria were: (1) they contained a rounded smooth perimeter suggestive of a membrane; (2) micronuclei were less than a third the diameter of the associated nucleus, but large enough to discern shape and color; (3) staining intensity was similar to that of the nucleus; (4) texture was similar to that of the nucleus; (5) they were in the same focal plane as the nucleus; and (6) an absence of overlap with, or bridge to, the nucleus. Furthermore, numerous studies of the research group have already been published with the micronucleus technique: in rodent models (da Silva Júnior et al, 2013a, 2013b; Garcia et al, 2016, 2017; Hort et al, 2019); amphibians (Josende et al, 2015); earthworms (da Silva Júnior et al, 2019); and humans (da Silva Júnior et al, 2018; da Silva Pinto et al, 2017). Finally, it is worth mentioning two other concerns addressed by our group to minimize possible errors or biases in our analyses: (1) the slides were photographed for, if necessary, a subsequent reinterpretation and (2) the entire reading of the slides was done blindly (each individual received a numeric code and the analyzer was unaware of the participant’s allocation within the groups).…”
mentioning
confidence: 99%
“…It should be noted that most of the works devoted to the study of genotoxic effects using the BMCyt assay in miners are related to coal mining [54,68,69,85,86]. In these works, the authors showed a significant increase in the frequency of MN in buccal epithelium cells in coal miners.…”
Section: Discussionmentioning
confidence: 98%
“…However, comet assay on various tissues is also used to assess DNA repair [65,66]. Thus, Brazilian researchers successfully combine the BMCyt assay and comet assay in human lymphocytes to assess genotoxicity and reparation when exposed to xenobiotics [67][68][69].…”
Section: Discussionmentioning
confidence: 99%